The Role of Cold-Sensitive Ion Channels in Peripheral Thermosensation - Buijs, Tamara Joëlle; McNaughton, Peter Anthony (Frontiers in Cellular Neuroscience, 2020)
The detection of ambient cold is critical for mammals, who use this information to avoid tissue damage by cold and to maintain a stable body temperature. The transduction of information about environmental cold is mediated by cold-sensitive ion channels expressed in peripheral sensory nerve endings in the skin. Most transduction mechanisms for detecting temperature changes identified to date depend on Transient Receptor Potential (TRP) ion channels. Mild cooling is detected by the menthol-sensitive TRPM8 ion channel, but how painful cold is detected remains unclear. The TRPA1 ion channel, which is activated by cold in expression systems, seemed to provide an answer to this question, but whether TRPA1 is activated by cold in neurons and contributes to the sensation of cold pain continues to be a matter of debate. Recent advances have been made in this area of investigation with the identification of several potential cold-sensitive ion channels in thermosensory neurons, including two-pore domain potassium channels (K2P), GluK2 glutamate receptors, and CNGA3 cyclic nucleotide-gated ion channels. This mini-review gives a brief overview of the way by which ion channels contribute to cold sensation, discusses the controversy around the cold-sensitivity of TRPA1, and provides an assessment of some recently-proposed novel cold-transduction mechanisms. Evidence for another unidentified cold-transduction mechanism is also presented.